The development of learning media to increase children saving interest - Mawarni Mawarni; Ria Novianti; Yeni Solviah (Atfaluna: Journal of Islamic Early Childhood Education, 2022)
This study aims to develop learning media to increase children's interest in saving. This research is a type of Research and Development (R&D) that refers to the Borg and Gall model in 10 stages. This media was subjected at 5-6 years old in Insan Utama Kindergarten, Pekanbaru. The data were collected through observation and interviews. The study results indicate that the learning media the researcher calls 'saving-alarm' is feasible to use after the validation stages by validators of material experts, media experts, and educators and also through a limited trial stage. Material validation got a feasibility percentage of 85%, media validation 83%, educator validation 88%, and a trial percentage of 94%. Therefore, learning 'saving-alarm' media can increase children's interest in saving. Research related to the development of alarm savings media can be investigated further for other aspects of development.